A Narrative Study: Understanding The Intersections Of Race, Class, Gender, And Sexuality In The Pathways To Crime And Incarceration In African American Women’s Lives - Stewart, Rachelle A (2018)
This thesis explores the intersections of race, class, gender, and sexuality in African American women’s lives and the way public policy intervenes in their pathways to crime and incarceration, by way of personal life histories. By exploring their personal life narratives allows for finding a voice that can express a self-defined black woman’s standpoint. Black women’s narratives offer a unique insight into interlocking patterns of oppression that contribute to their incarceration, and how discrimination based on race, gender, and sexuality extends into prison. Through the collection of five in-depth interviews, I examined how certain themes and how the intersection of social and structural factors told through their very own stories influences their criminal decision-making. Using a Black Feminist Thought framework is essential to capture black women’s experiences as both offenders and women who live through the collateral consequences of mass incarceration